If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 11 = 8 Reorder the terms: 11 + z = 8 Solving 11 + z = 8 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + z = 8 + -11 Combine like terms: 11 + -11 = 0 0 + z = 8 + -11 z = 8 + -11 Combine like terms: 8 + -11 = -3 z = -3 Simplifying z = -3
| 98-6x=12x+20 | | -3x+5=-6+x | | 12-8x=80-36x | | a+12=20 | | d-7=-9 | | -75-7x=8x+15 | | 3x+10=52-3x | | 6x+8=-24-10x | | 2x=-10 | | 10+g=10 | | 4x-2=11x-37 | | 151-4x=6x+21 | | 3x+36=11x-44 | | 10n=9n+22 | | 2z=2 | | 3z+3=9 | | 10x-17=7x+1 | | a+10=1 | | 37-6x=13 | | 2z+5=13 | | x+121=4(x-5) | | 10+a=1 | | 7+w=4 | | 2x+69=7x+14 | | x-12=-3 | | 8x=9(x-2) | | 17x-8x-11=100-30 | | 8x+6=6x+20 | | -41-2x=7-8x | | 4x-14=2x | | x+(-12)=3 | | -13x=78 |